Experimental Evaluation of Wear Resistance of Polymer Materials Used in Piston Compressor Equipment - Aleksey S. Brundukov; Yaroslava A. Kavaliova (Механика машин, механизмов и материалов, 2024)
A new method is proposed for assessing the wear resistance of polymer materials according to the “finger — disk” friction scheme. It involves changing the geometry of the friction zone of polymer samples — the “finger” sphere is replaced by a truncated cone. The developed method is tested on samples of polyetheretherketone (PEEK) and polymer composite materials (PCM) based on polytetrafluoroethylene (PTFE, fluoroplast-4), in particular, obtained after laser ablation with the addition of carbon fibers. The relevance lies in simplifying the manufacture of samples, as well as the possibility of quickly changing the geometric parameters of their working part, which expands the scope of the method with respect to the latest polymer materials and composites based on them. The practical significance of the results is confirmed by their use at such enterprises as JSC “Grodno Azot” and JSC “Grodno Mechanical Plant”, which serially produce tribotechnical PCM.